QUESTIONING THE LEGALIZATION OF THE DISMISSAL OF ADVOCATES BY THE SUPREME COURT - Rival Pramudya; Putri Sindi Rinata; Bella Putri Nabillah; Herry Frediono Romdhon (Ann Publisher, 2025)
Abstract: Background. As one of the main elements in the legal system, advocates have a crucial role in upholding the rule of law in Indonesia. Their duties are not only limited to legal defense, but also include contributions to creating a fair, transparent, and legally certain judicial system. Aims. This study aims to evaluate in depth the legality of the Supreme Court's actions in removing advocates from their positions. Methods. This study uses a normative juridical approach, using secondary data as the primary source. The data includes an Ambon High Court Number 44/KPT decree. W27-U/HM. 1. 1. 1/II/2025 and Banten High Court Number 52/KPT. W29/HM. 1. 1. 1/II/2025, Law Number 18 of 2003 concerning Advocates, and various relevant academic references. The data collection method is done through literature studies and legal document reviews. The analysis is carried out qualitatively with a normative approach to assess the suitability of the actions of judicial institutions with the applicable legal provisions. Result. The results of the analysis show that there is a disorientation in the application of procedural law, even though facts are found that support the violation of the law and professional ethics. Conclusion. This indicates that the legal process carried out has not fully prioritized the principles of justice and legal certainty as mandated in the judicial system in Indonesia. Implementation. The disparity between violations and sanctions enforcement shows that procedural law has not only been procedurally flawed but has also ignored fundamental values such as justice, legal certainty, and institutional accountability. This condition requires a thorough evaluation of procedural law's implementation to build a legal system that is more integrity and responsive to substantive justice.